Testing therapeutics in cell-based assays: Factors that influence the apparent potency of drugs. - Elena Postnikova; Yu Cong; Lisa Evans DeWald; Julie Dyall; Shuiqing Yu; Brit J Hart; Huanying Zhou; Robin Gross; James Logue; Yingyun Cai; Nicole Deiuliis; Julia Michelotti; et al. (PLoS ONE, 2018)
Identifying effective antivirals for treating Ebola virus disease (EVD) and minimizing transmission of such disease is critical. A variety of cell-based assays have been developed for evaluating compounds for activity against Ebola virus. However, very few reports discuss the variable assay conditions that can affect the results obtained from these drug screens. Here, we describe variable conditions tested during the development of our cell-based drug screen assays designed to identify compounds with anti-Ebola virus activity using established cell lines and human primary cells. The effect of multiple assay readouts and variable assay conditions, including virus input, time of infection, and the cell passage number, were compared, and the impact on the effective concentration for 50% and/ or 90% inhibition (EC50, EC90) was evaluated using the FDA-approved compound, toremifene citrate. In these studies, we show that altering cell-based assay conditions can have an impact on apparent drug potency as measured by the EC50. These results further support the importance of developing standard operating procedures for generating reliable and reproducible in vitro data sets for potential antivirals.